Composite dispersing agent as well as preparation method and application thereof
By using composite dispersant in the negative electrode sheet of lithium-ion battery, the problem of cracking and curling of the negative electrode sheet during coating and drying is solved, and the flexibility of the electrode sheet is improved, achieving better battery performance.
Patent Information
- Application Number
- CN202411915481.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art can easily lead to cracking and curling problems during the coating and drying of the negative electrode sheet of lithium-ion battery, and it is difficult to achieve increased flexibility of the electrode sheet.
A composite dispersant is used, which consists of the first component and the second component. Through coordinated cooperation, the surface tension of the negative electrode slurry is reduced, the solvent evaporation rate is uniformly controlled, the electrode sheet is avoided cracking and curling, and the electrode sheet is improved.
It effectively avoids cracking and curling problems caused by local drying of the wet film of the electrode sheet, and at the same time improves the flexibility of the negative electrode sheet, with a bending diameter of less than 6mm.
Smart Images

Figure CN119725366A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a composite dispersant and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their advantages such as high energy density, high operating voltage, wide application temperature range and long cycle life.
[0003] Lithium-ion batteries are composed of positive electrodes, negative electrodes, separators and electrolytes. During molding, the prepared slurry needs to be coated on aluminum foil and copper foil respectively to make positive and negative electrodes. Therefore, the composition and characteristics of the slurry are directly related to the quality of the coating. In view of the increasingly high requirements for the capacity of lithium batteries, the usual solution is to increase the proportion of electrode active substances in the slurry or to apply a thicker slurry. However, increasing the proportion of electrode active substances in the slurry will involve the problem of slurry fluidity. After the slurry is thickly applied, it is easy to leak or crack when winding and folding, so it is necessary to increase the flexibility of the electrode.
[0004] At present, the industry has a practice of adding plasticizers such as dimethyl phthalate, dioctyl phthalate, etc. to the positive electrode slurry of the battery to increase the toughness of the slurry and thus achieve the purpose of softening. However, the amount of plasticizer added is high and the volatilization is not complete. The residual plasticizer is likely to affect the performance of the electrolyte; plasticizers such as phosphate triesters and citrate triesters can increase the flexibility by reducing the stress of the binder, but the ductility is limited when thickly coated, and it is easy to increase the viscosity of the slurry system; polyethylene glycol, epoxy soybean oil, etc. all contain a large number of active hydroxyl groups, which are easy to swell when remaining in the slurry; adding small molecule alcohols or nitrogen methyl pyrrolidone to the negative electrode slurry of the battery can reduce the surface tension during the coating and drying process to achieve the purpose of anti-cracking and toughening, but the volatilization process of this type of additive will cause environmental pollution, and after volatilization, it can no longer play a toughening role.
[0005] Therefore, how to solve the cracking and curling problems of the negative electrode sheet and improve the flexibility of the negative electrode sheet is the focus of current research. Summary of the invention
[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a composite dispersant and its preparation method and application. The present invention provides a new type of composite dispersant, which effectively reduces the surface tension of the negative electrode slurry through the synergistic cooperation of the first component and the second component of the above structural formula, not only making the solvent evaporation rate of the negative electrode slurry uniform during the drying process, avoiding the problem of cracking and curling of the electrode sheet caused by excessive local drying of the electrode sheet wet film, but also improving the flexibility of the negative electrode sheet, and its anti-bending diameter is less than 6mm in the winding test.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a composite dispersant, the composite dispersant comprising a first component and a second component, wherein the chemical structural formula of the first component is:
[0009] Wherein, R1 is selected from any one of -CH3, -COOH, -NH2 or -SO3H, and R2 is selected from any one of -NH2, -CHO, -SO3H, -OH, -COOH, -PO3H2, Or any one of quaternary ammonium salt groups, n is 1-20.
[0010] The chemical structural formula of the second component is:
[0011] (CH3)2(R3)Si-O-(Si(CH3)2-O) x -Si(CH3)2(R4), or
[0012] (CH3)3Si-O-(Si(CH3)2-O) y -(Si(CH3)(R5)-O) z -Si(CH3)3; wherein R3, R4 and R5 are each independently selected from -NH2, -SO3H, -OH or -COOH or Any one of the above, wherein the value ranges of x, y and z are independently 1-20.
[0013] The mass fraction ratio of the first component to the second component is (30-70):(70-30).
[0014] The present invention provides a novel composite dispersant, which effectively reduces the surface tension of the negative electrode slurry through the synergistic cooperation of the first component and the second component of the above structural formula, not only making the solvent evaporation rate of the negative electrode slurry uniform during the drying process, avoiding the problem of cracking and curling of the electrode piece caused by local excessive drying of the electrode wet film, but also improving the flexibility of the negative electrode electrode piece. In the winding test, its anti-bending diameter is less than 6 mm.
[0015] In the present invention, the value of n is 1-20, for example, 1, 5, 10, 15 or 20, and the value ranges of x, y and z are independently 1-20, for example, 1, 5, 10, 15 or 20. The quaternary ammonium salt group may be, for example, (CH3)4N-.
[0016] In the present invention, the mass fraction ratio of the first component to the second component is (30-70): (70-30), wherein the mass fraction selection range of the first component "30-70" can be, for example, 30, 40, 50, 60 or 70, and the mass fraction selection range of the second component "70-30" can be, for example, 30, 40, 50, 60 or 70. The first component and the second component with a suitable ratio can more effectively reduce the surface tension of the negative electrode slurry, improve the flexibility of the negative electrode sheet, and avoid the problems of cracking and curling of the negative electrode sheet.
[0017] Preferably, the R1 is -CH3, the R2 is
[0018] In the present invention, As The grafted modified group has excellent water solubility, which is beneficial to reducing the surface tension of the negative electrode slurry, so that during the drying process after the negative electrode slurry is coated, the evaporation rate of the solvent (water) is uniform, effectively avoiding the problem of cracking of the negative electrode sheet.
[0019] It should be noted that Where R1 is -CH3, R2 is The structure at the time is an existing product purchased from Angxing New Carbon Materials Changzhou Co., Ltd., and its CAS number is 92451-00-8.
[0020] Preferably, the second component is (CH3)3Si-O-(Si(CH3)2-O) y -(Si(CH3)(R5)-O) z -Si(CH3)3, R5 is
[0021]
[0022] It should be noted that (CH3)3Si-O-(Si(CH3)2-O) y -(Si(CH3)(R5)-O) z -Si(CH3)3 R5 is The structure at the time is an existing product, and its CAS number is 68938-54-5.
[0023] In the present invention, the grafting of the above-mentioned modified groups helps to improve the hydrophilicity of the second component, effectively reduces the surface tension of the negative electrode slurry, improves the surface uniformity during the drying process, and prevents cracking.
[0024] Preferably, the mass fraction ratio of the first component to the second component is (40-60):(60-40), wherein the mass fraction selection range of the first component "40-60" can be, for example, 40, 45, 50, 55 or 60, etc., and the mass fraction selection range of the second component "60-40" can be, for example, 40, 45, 50, 55 or 60, etc.
[0025] In a second aspect, the present invention provides a method for preparing the composite dispersant as described in the first aspect, the preparation method comprising the following steps:
[0026] The first component and the second component are mixed to obtain the composite dispersant.
[0027] Preferably, the mixing process is accompanied by stirring.
[0028] Preferably, the stirring speed is 300-2000 rpm, for example, it can be 300 rpm, 400 rpm, 500 rpm, 1000 rpm, 1500 rpm or 2000 rpm.
[0029] Preferably, the mixing time is 30-90 min, for example, 30 min, 60 min or 90 min.
[0030] Preferably, during the mixing process, the temperature is 15-80°C, for example, 15°C, 20°C, 25°C, 50°C, 60°C, 70°C or 80°C.
[0031] In the present invention, mixing the first component and the second component within the above-mentioned suitable temperature range is helpful for the two components to be fully mixed to form a homogeneous phase material, and problems such as product separation or uneven dissolution rate will not occur.
[0032] In a third aspect, the present invention provides a negative electrode slurry, which includes a negative electrode active material, a binder, a conductive agent, a solvent and the composite dispersant as described in the first aspect.
[0033] Preferably, the negative electrode slurry comprises, by weight:
[0034] 3000-3500 parts of negative electrode active material, 50-60 parts of slurry stabilizer, 30-35 parts of conductive agent, 20-50 parts of composite dispersant, 2500-3000 parts of solvent, and 100-150 parts of binder glue.
[0035] In the present invention, the number of parts of the negative electrode active material can be, for example, 3000 parts, 3100 parts, 3200 parts, 3300 parts, 3400 parts or 3500 parts, the number of parts of the slurry stabilizer can be, for example, 50 parts, 55 parts or 60 parts, the number of parts of the binder glue can be, for example, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts or 150 parts, the number of parts of the conductive agent can be, for example, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts, and the number of parts of the solvent can be, for example, 2500 parts, 2600 parts, 2700 parts, 2800 parts, 2900 parts or 3000 parts, etc.
[0036] In the present invention, the number of parts of the composite dispersant can be, for example, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, etc. If the number of parts of the composite dispersant in the negative electrode slurry is too small, it is not conducive to the control of the surface tension of the slurry, resulting in the dispersant being unable to function normally, and further resulting in the occurrence of adverse phenomena such as cracking of the polar film during the drying process. If the number of parts of the composite dispersant in the negative electrode slurry is too large, it has no effect on the cracking effect, but is not conducive to the process formula design and cost control.
[0037] Preferably, the negative electrode active material includes graphite material or silicon-carbon material.
[0038] Preferably, the slurry stabilizer comprises carboxymethyl cellulose.
[0039] Preferably, the adhesive glue comprises styrene-butadiene rubber glue.
[0040] Preferably, the conductive agent includes any one of conductive carbon black, carbon nanotubes or graphene, or a combination of at least two of them.
[0041] Preferably, the solvent includes water, for example, deionized water.
[0042] In a fourth aspect, the present invention provides a method for preparing the negative electrode slurry as described in the third aspect, the preparation method comprising the following steps:
[0043] The negative electrode active material, slurry stabilizer, conductive agent, solvent, composite dispersant and binder glue are mixed to obtain the negative electrode slurry.
[0044] Preferably, the solvent is divided into two parts, including a first solvent and a second solvent; and the mixing method includes:
[0045] (a) A negative electrode active material, a slurry stabilizer, a conductive agent and a first solvent are mixed to obtain a mixed solution.
[0046] (b) adding the composite dispersant and the second solvent into the mixed solution and mixing them, and then adding the binder glue solution and continuing to mix.
[0047] In a fifth aspect, the present invention provides a negative electrode plate, which is obtained by coating the negative electrode slurry described in the third aspect on a negative electrode current collector and then drying it.
[0048] In the process of drying after coating the negative electrode slurry provided by the present invention on the negative electrode current collector, the evaporation rate of the solvent (water) is uniform, which can effectively avoid the problem of the electrode sheet cracking caused by the local drying of the electrode sheet wet film too fast. At the same time, the flexibility of the obtained negative electrode sheet is improved to a certain extent. In the winding test, its anti-bending diameter is less than 6mm.
[0049] In a sixth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate as described in the fifth aspect.
[0050] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The present invention provides a novel composite dispersant, which effectively reduces the surface tension of the negative electrode slurry through the synergistic cooperation of the first component and the second component of the above structural formula, not only making the solvent evaporation rate of the negative electrode slurry uniform during the drying process, avoiding the problem of cracking and curling of the electrode piece caused by local excessive drying of the electrode wet film, but also improving the flexibility of the negative electrode electrode piece. In the winding test, its anti-bending diameter is less than 6 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a schematic diagram of the negative electrode sheet provided in Example 1 of the present invention.
[0054] Figure 2 This is a schematic diagram of the negative electrode sheet provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Example 1
[0057] This embodiment provides a composite dispersant, which includes a first component and a second component, wherein the chemical structural formula of the first component is:
[0058] Wherein, R1 is -CH3, R2 is n is 10.
[0059] The chemical structural formula of the second component is:
[0060] (CH3)3Si-O-(Si(CH3)2-O) y -(Si(CH3)(R5)-O) z -Si(CH3)3, wherein R5 is The CAS number is 68938-54-5.
[0061] The mass fraction ratio of the first component to the second component is 50:50.
[0062] This embodiment also provides a method for preparing the composite dispersant, the preparation method comprising the following steps:
[0063] The first component and the second component were mixed at a temperature of 60° C. and stirred at a rotation speed of 800 rpm for 60 minutes to obtain the composite dispersant.
[0064] This embodiment further provides a negative electrode slurry, which comprises, by weight:
[0065] 3100 parts of negative electrode active material, 55 parts of slurry stabilizer, 33 parts of conductive agent, 33 parts of composite dispersant, 2800 parts of solvent, and 120 parts of binder glue.
[0066] The negative electrode active material is artificial graphite, the slurry stabilizer is carboxymethyl cellulose, the binder glue is styrene-butadiene rubber glue, the conductive agent is conductive carbon black, and the solvent is deionized water.
[0067] This embodiment also provides a method for preparing the negative electrode slurry, the preparation method comprising the following steps:
[0068] (1) artificial graphite powder, conductive carbon black, carboxymethyl cellulose and deionized water (weight ratio of 3100:33:55:1600) were added to a double planetary stirring tank and mixed at a stirring speed of 40 rpm, a dispersion speed of 1000 rpm and a mixing time of 30 min to obtain a first mixed solution;
[0069] (2) adding 33 parts of the composite dispersant and 1200 parts of deionized water to the first mixed solution and mixing for 60 minutes, wherein the stirring speed is 35 rpm and the dispersion speed is 3000 rpm, to obtain a second mixed solution;
[0070] (3) 120 parts of styrene-butadiene rubber solution were added to the second mixed solution and mixed for 20 minutes. During the mixing process, the stirring speed was 30 rpm and the dispersion speed was 1000 rpm to obtain a negative electrode slurry.
[0071] This embodiment also provides a negative electrode plate, which is obtained by coating the negative electrode slurry on a copper foil of size 12 cm×30 cm with a 750 μm scraper and then drying. The drying temperature is 100° C. and the drying time is 15 min.
[0072] Example 2
[0073] This embodiment provides a composite dispersant, and the composition of the composite dispersant is the same as that of Embodiment 1.
[0074] The mass fraction ratio of the first component to the second component is 40:60.
[0075] This embodiment also provides a method for preparing the composite dispersant, the preparation method comprising the following steps:
[0076] The first component and the second component were mixed at a temperature of 80° C. and stirred at a rotation speed of 300 rpm for 90 minutes to obtain the composite dispersant.
[0077] This embodiment further provides a negative electrode slurry, which comprises, by weight:
[0078] 3100 parts of negative electrode active material, 50 parts of slurry stabilizer, 35 parts of conductive agent, 50 parts of composite dispersant, 2500 parts of solvent, and 100 parts of binder glue.
[0079] The negative electrode active material is artificial graphite, the slurry stabilizer is carboxymethyl cellulose, the binder glue is styrene-butadiene rubber glue, the conductive agent is conductive carbon black, and the solvent is deionized water.
[0080] This embodiment also provides a method for preparing the negative electrode slurry, the preparation method comprising the following steps:
[0081] (1) artificial graphite powder, conductive carbon black, carboxymethyl cellulose and deionized water (weight ratio of 3100:35:50:1500) were added to a double planetary stirring tank and mixed at a stirring speed of 40 rpm, a dispersion speed of 1000 rpm, and a mixing time of 30 min to obtain a first mixed solution;
[0082] (2) adding 50 parts of the composite dispersant and 1000 parts of deionized water to the first mixed solution and mixing for 60 minutes, wherein the stirring speed is 35 rpm and the dispersion speed is 3000 rpm, to obtain a second mixed solution;
[0083] (3) 100 parts of styrene-butadiene rubber solution were added to the second mixed solution and mixed for 20 minutes. During the mixing process, the stirring speed was 30 rpm and the dispersion speed was 1000 rpm to obtain a negative electrode slurry.
[0084] This embodiment also provides a negative electrode plate, which is obtained by coating the negative electrode slurry on a copper foil of size 12 cm×30 cm with a 750 μm scraper and then drying. The drying temperature is 100° C. and the drying time is 15 min.
[0085] Example 3
[0086] This embodiment provides a composite dispersant, the composition of the composite dispersant is the same as that of Embodiment 1, and the mass fraction ratio of the first component to the second component is 60:40.
[0087] This embodiment also provides a method for preparing the composite dispersant, the preparation method comprising the following steps:
[0088] The first component and the second component were mixed at a temperature of 40° C. and stirred at a rotation speed of 2000 rpm for 30 minutes to obtain the composite dispersant.
[0089] This embodiment further provides a negative electrode slurry, which comprises, by weight:
[0090] 3100 parts of negative electrode active material, 60 parts of slurry stabilizer, 30 parts of conductive agent, 20 parts of composite dispersant, 3000 parts of solvent, and 150 parts of binder glue.
[0091] The negative electrode active material is artificial graphite, the slurry stabilizer is carboxymethyl cellulose, the conductive agent is conductive carbon black, the solvent is deionized water, and the binder glue is styrene-butadiene rubber glue.
[0092] This embodiment also provides a method for preparing the negative electrode slurry, the preparation method comprising the following steps:
[0093] (1) artificial graphite powder, conductive carbon black, carboxymethyl cellulose and deionized water (weight ratio of 3100:30:60:1700) were added to a double planetary stirring tank and mixed at a stirring speed of 40 rpm, a dispersion speed of 1000 rpm and a mixing time of 30 min to obtain a first mixed solution;
[0094] (2) adding 20 parts of the composite dispersant and 1300 parts of deionized water to the first mixed solution and mixing for 60 minutes, wherein the stirring speed is 35 rpm and the dispersion speed is 3000 rpm, to obtain a second mixed solution;
[0095] (3) 150 parts of styrene-butadiene rubber solution were added to the second mixed solution and mixed for 20 minutes. During the mixing process, the stirring speed was 30 rpm and the dispersion speed was 1000 rpm to obtain a negative electrode slurry.
[0096] This embodiment also provides a negative electrode plate, which is obtained by coating the negative electrode slurry on a copper foil of size 12 cm×30 cm with a 750 μm scraper and then drying. The drying temperature is 100° C. and the drying time is 15 min.
[0097] Example 4
[0098] The difference between this embodiment and embodiment 1 is that the mass fraction ratio of the first component to the second component is 30:70.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Example 5
[0101] The difference between this embodiment and embodiment 1 is that the mass fraction ratio of the first component to the second component is 70:30.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Example 6
[0104] The difference between this embodiment and embodiment 1 is that in the negative electrode slurry, the number of parts of the composite dispersant is 15 parts.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Example 7
[0107] The difference between this embodiment and embodiment 1 is that in the negative electrode slurry, the number of parts of the composite dispersant is 200 parts.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 1 is that the composite dispersant contains only the first component.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Figure 1 and Figure 2Schematic diagrams of negative electrode sheets provided in Example 1 and Comparative Example 1 are respectively shown. By comparison, it can be seen that compared with the present application, the negative electrode sheet provided in Comparative Example 1 has problems such as sheet cracking and curling.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that the composite dispersant contains only the second component.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is that in the composite dispersant, the mass fraction ratio of the first component to the second component is 20:80.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 4
[0120] The difference between this comparative example and Example 1 is that in the composite dispersant, the mass fraction ratio of the first component to the second component is 80:20.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Performance Testing
[0123] The negative electrode sheets provided in the above-mentioned embodiments and comparative examples were tested.
[0124] 1. Visually observe the negative electrode to see if there are any cracks, breaks, edge lift or other defects.
[0125] 2. Test the bending resistance of the negative electrode sheet by cylindrical winding. The specific methods include:
[0126] Cut the negative electrode sheet into 2cm×12cm, with the negative electrode material facing outward, and wind it on the surface of cylinders of different diameters (the diameters of the cylinders used are 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm and 16mm). After unfolding, observe whether there are cracks or breaks, and record the diameter of the cylinder where cracks begin to appear as the upper limit of cracking.
[0127] The above test results are shown in Table 1.
[0128] Table 1
[0129]
[0130] analyze:
[0131] It can be seen from the above table that the composite dispersant provided by the present invention effectively reduces the surface tension of the negative electrode slurry, which not only makes the solvent evaporation rate of the negative electrode slurry uniform during the drying process, avoiding the problems of cracking and curling of the electrode sheet caused by local drying of the electrode wet film too fast, but also improves the flexibility of the negative electrode sheet. In the winding test, its anti-bending diameter is less than 6mm.
[0132] By comparing Example 1 and Examples 6-7, it can be seen that if the proportion of the composite dispersant in the negative electrode slurry is too small, it will not be conducive to the anti-cracking effect, and serious cracking will occur during the drying process of the electrode. In actual use, there is a lower limit requirement for the amount of composite dispersant added; if the proportion of the composite dispersant in the negative electrode slurry is too large, it will have no adverse effect on the drying process of the electrode, but too much addition is not conducive to cost control. In actual use, the maximum addition amount needs to be controlled according to the equipment and process conditions.
[0133] By comparing Example 1 and Comparative Examples 1-2, it can be seen that if the composite dispersant contains only the first component, the synergistic effect of the two components will be weakened, small cracks will appear in the local area of the pole film during the drying process, and the flexibility of the dry film in the uncracked area will also be reduced in the winding test; if the composite dispersant contains only the second component, the synergistic effect of the two components will be weakened, small cracks will appear in the local area of the pole film during the drying process, and the flexibility of the dry film will be seriously reduced.
[0134] From the comparison of Example 1, Examples 4-5 and Comparative Examples 3-4, it can be seen that if the mass fraction ratio of the first component to the second component in the composite dispersant is too small, it is not conducive to the synergistic effect of the two types of molecules in the process of reducing surface tension, and there are defects in the internal structure of the dry film. Due to the low content of the first component, the flexibility of the dry film decreases significantly; if the mass fraction ratio of the first component to the second component in the composite dispersant is too large, it is also not conducive to the synergistic effect of the two types of molecules in the process of reducing surface tension, and there are defects in the internal structure of the dry film. Due to the high content of the first component, the decrease in the flexibility of the dry film is slightly smaller than the normal ratio.
[0135] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite dispersant, characterized in that: The composite dispersant comprises a first component and a second component, wherein the chemical structural formula of the first component is: Wherein, R1 is selected from any one of -CH3, -COOH, -NH2 or -SO3H, and R2 is selected from any one of -NH2, -CHO, -SO3H, -OH, -COOH, -PO3H2, Or any one of quaternary ammonium salt groups, n is 1-20; The chemical structural formula of the second component is: (CH3)2(R3)Si-O-(Si(CH3)2-O) x -Si(CH3)2(R4), or (CH3)3Si-O-(Si(CH3)2-O) y -(Si(CH3)(R5)-O) z -Si(CH3)3; wherein R3, R4 and R5 are each independently selected from -NH2, -SO3H, -OH or Any one of the above, wherein the value ranges of x, y and z are independently 1-20; The mass fraction ratio of the first component to the second component is (30-70):(70-30).
2. The composite dispersant according to claim 1, characterized in that The R1 is -CH3, the R2 is And / or, said R3, R4 and R5 are all -R6-(OCH2CH2) m -O-R7; And / or, the mass fraction ratio of the first component to the second component is (40-60):(60-40).
3. A method for preparing the composite dispersant as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: The first component and the second component are mixed to obtain the composite dispersant.
4. The preparation method according to claim 3, characterized in that: The mixing process is accompanied by stirring; And / or, the stirring speed is 300-2000 rpm; And / or, the mixing time is 30-90min; And / or, during the mixing process, the temperature is 15-80°C.
5. A negative electrode slurry, characterized in that: The negative electrode slurry comprises a negative electrode active material, a slurry stabilizer, a binder glue, a conductive agent, a solvent and the composite dispersant as claimed in claim 1 or 2.
6. The negative electrode slurry according to claim 5, characterized in that: The negative electrode slurry comprises, by weight: 3000-3500 parts of negative electrode active material, 50-60 parts of slurry stabilizer, 30-35 parts of conductive agent, 20-50 parts of composite dispersant, 2500-3000 parts of solvent, and 100-150 parts of binder glue.
7. A method for preparing a negative electrode slurry according to claim 5 or 6, characterized in that: The preparation method comprises the following steps: The negative electrode active material, a slurry stabilizer, a conductive agent, a solvent, a composite dispersant and a binder glue are mixed to obtain the negative electrode slurry.
8. The preparation method according to claim 7, characterized in that: The solvent is divided into two parts, including a first solvent and a second solvent; The mixing method includes: (a) mixing a negative electrode active material, a slurry stabilizer, a conductive agent and a first portion of the solvent to obtain a mixed solution; (b) adding the composite dispersant and the second solvent into the mixed solution and mixing them, and then adding the binder glue solution and continuing to mix.
9. A negative electrode plate, characterized in that: The negative electrode sheet is obtained by coating the negative electrode slurry according to claim 5 or 6 on a negative electrode current collector and then drying it.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9.